2014 European guideline on the management of syphilis - Janier, M.; Hegyi, V.; Dupin, N.; Unemo, M.; Tiplica, G.S.; Potocnik, M.; French, P.; Patel, R. (Dermatology Review/Przegląd Dermatologiczny, 2015)
Reprinted and translated from Journal of the European Academy of Dermatology and Venereology 28 (2014) “2014 European guideline on the management of syphilis” pp. 1581-1593, Copyright 2014 with permission © 2014 European Academy of Dermatology and Venereology. Background. Syphilis remains a major public health problem in Europe (both in Eastern Europe since the 1990’s and in Western Europe since the re-emergence of the disease in the late 1990’s-early 2000’s). Methods. This guideline is an update of the IUSTI: 2008 European guideline on the management of syphilis and is produced by the European Guideline Editorial Board (http://www.iusti.org/regions/Europe/pdf/2013/Editorial_Board.pdf) and EDF Guideline Committee. Results . It provides recommendations concerning the diagnosis and management of syphilis in Europe. Major advances include (1) broader use of PCR, immunohistochemistry, subtyping of the etiological agent Treponema pallidum subspecies pallidum, new treponemal tests, and rapid-point-of-care (POC) tests detecting both treponemal and non-treponemal antibodies, (2) more flexible options for screening (TT-treponemal test – first or NTT – non treponemal test – first or both TT and NTT), and (3) procaine penicillin is no longer the first line therapy option in any phase of the disease, i.e. long acting penicillin G (i.e. benzathine penicillin G-BPG) is the only first line therapy regimen in early syphilis and in late latent syphilis. Conclusions . Syphilis is a disease that is relatively easy to detect by appropriate serological tests, however, all laboratory results should be considered together with clinical data and sexual risk anamnesis. Syphilis is also easy to treat with BPG. A major concern about the supply of BPG in many European countries could threaten the efficacy of the policies of eradication of the disease in Europe.